Preparation and characterization of polyaniline (PANI)-Mn3O4 nanocomposite - Durmus, ZEHRA; Baykal, A.; Kavas, H.; SOZERI, H. (My University, 2011)
Polyaniline (PANI)-Mn3O4 nanocomposite was synthesized by a combination of sonochemical synthesis of Mn3O4 NP-s and in-situ polymerization of aniline. Structural characteristics were evaluated by XRD, FT-IR, TGA, VSM, TEM and SEM analysis, and conduction characteristics were evaluated by total conductivity measurements in the temperature range of 20-100 degrees C and frequency range of 0.1 Hz-1 MHz. Our findings show that PANI is successfully coated on nanoparticles surface and overall conductivity of nanocomposite is approximately 50-1000 times higher than that of uncapped Mn3O4 or PANI base with increase in temperature. Morphology of the synthesized powder was observed to be thin nanosheets with a thickness of 2-3 nm based on SEM analysis. Room temperature magnetization curves for nanocomposite show no hysteresis, indicating the super-paramagnetic character of the sample in the region of measured field strength. sigma(AC) increased after polyaniline coating. (C) 2011 Elsevier B.V. All rights reserved.